Dialogue between Canon Law and Law in Postmodern Europe - Gałkowski, Tomasz Robert (Ecumeny and law, 2024)
The world today is described as postmodern. However, the forms of reli- gious life still present in it allow it to be seen as post-secular. The programmatic removal of religion from social life has not achieved results. The continued pres- ence of religion brings its characteristic values to social life. The world can draw on its unique normative intuition as expressed by Jürgen Habermas. The norma- tive dimension of religion is also constituted by its law. For this reason, a reflec- tion has been undertaken on the possibility of a dialogue between the law of the Church and the law in the world, in its postmodern view. An area of possible dia- logue is the unity of the idea of law expressed in the plurality of legal orders. The determinants of this idea include, among others, equity, legal security and justice, which were presented as reference points for the possibility of dialogue between law and canon law.